THE INFLUENCE OF SELF-CONFIDENCE ON THE PERFORMANCE OF SOCIAL SCIENCE TEACHERS IN THE NEW KEBAYORAN SUB-DISTRICT OF SOUTH JAKARTA, INDONESIA - Heru Sriyono (International Journal of Research Science and Management, 2018)
This study aims to determine the influence of Self Confidence in the Performance of Social Science Teachers. The research method used is a survey, a sample of 45 teachers selected randomly from all teachers of IPS South Jakarta. The data were collected by technique with questionnaire distribution, data analysis by statistical method Test statistic Test t. The result: Ŷ = 126,879 + 0.166X, Constant of 126,879 states that if the independent variable is considered constant, then the average Y will increase by 126.879. The regression coefficient X of 0.166 states that every addition of X is 1 point, then Y will increase equal to 127,045. This means that the confidence variable influences the IPS Teacher Performance variable.